PELAKSANAAN MANAJEMEN KEMITRAAN PT BUANA WIRALESTARI MAS DENGAN PETANI SAWIT DALAM PROGRAM REPLANTING SAWIT DI DESA KIJANG MAKMUR KECAMATAN TAPUNG HILIR - Resti Yuliandari; Harapan Tua R.F.S (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The replanting process is done to replace the unproductive plants with new plants gradually and thoroughly. This process uses a one-stop management pattern. This pattern is more secure to run a better replanting program.This study aims to inform the farmers that the replanting program is important for the future prosperity of farmers. PT Buana WiraLestari Mas itself has been 25 years partners with farmers in improving their palm products. And the benefits of replanting this results can be enjoyed by farmers in the long run. Because the program is run well by the PT and the Village Government so it will not disappoint the farmers.From the results of research shows that PT Buana WiraLestari and KUD really do their job well. During the replanting process they are responsible for the fate of the farmers who lost their income while PT Buana WiraLestari Mas tries the Cost of Living Gang for farmers in the form of replacement money during replanting of 500,000 per hectare per month.Keywords: Implementation, Partnership, replanting of oil palm.